Simbol Dalam Motif Ragam Hias Perisai Pada Suku Dayak Taman - Dismas Kwirinus (Universitas Muhammadiyah Makassar, 2024)
The focus of this research examines the symbols in various decorative shield motifs of the Taman Dayak tribe. The topic of study is related to the concept of decorative shield motifs in the Taman Dayak tribe. The shield of the Taman Dayak tribe is called Jabang or Kelau. Jabang (adjective) means a shield or protector who guards or protects. Kelau (noun) means shield as an object. As an object to decorate household furniture. For the Dayak Taman tribe, shields were used as body protection against spears, sabers or chopsticks during past wars. Seeing its function as a protective band, the shield must be made of strong material, not easily broken, broken, destroyed and light enough so that it is easy to use. The researcher used descriptive qualitative methods and critical reading of the text, namely: (1) Cultural philosophy books related to understanding the concept of symbolic motifs of the decorative shield motifs of the Taman Dayak tribe; (2) Articles that concentrate on studying the concept of motif symbols. The findings in this research are that the concept of symbols in the decorative motifs on the shields of the Dayak Taman tribe is a decoration that is believed to bring good luck to the wearer. The webbing is used to strengthen the shield as well as for its beauty. Nowadays, shields have changed their function from protective equipment to decoration, from weapons of war to traditional dance instruments. However, it is good to preserve the existing decorations, because they contain messages of wisdom about the harmony of life in the universe.